Consumer Preference on Catfishes (Patin and Lele) Sweetmeat Product. (July 2019) - Sundari, R S; Umbara, D S; Fitriadi, B W; Sulaeman, M
Abstract: Catfish sweetmeat is a new innovation of sweetmeat as food diversification made of catfish bream. To find out a product if it is able or not to meet consumer's necessity measured by preference on those products. This research aimed to indentfy consumer's preference on two sweetmeat catfish. The raw materials are such lele and patin by those atributes influenced to consumer due to decide to buy the producct. The method used Conjoint Analysis. The result determined that consumer prefer to decide to eat Patin than Lele catfish though higher price. Consumer rather confuse because of those are economic in price. Those both of catfishes are cheaper than beef in the market. The better taste of sweetmeat catfish the more prefer to eat. They said, why not to eat catfish that have the same taste as others even those have soft texture and easier to digest.